Factors affecting farmland sales in rural northern Thailand - Anupong Wongchai (2018)
© 2015 American Scientific Publishers. All rights reserved. Farmland areas have approximately accounted for 38.75 percent of the whole lands in Thailand. However, the number of farmlands has gradually decreased year by year due to an expansion of the industrial development projects. The study aimed to analyze the factors affecting the farmland sales in 17 northern provinces of Thailand, using an analysis of proportion data based on Logit model. Panel data were collected in ten harvest years starting from 2001/02 to 2013/14, recorded by the Office of Agricultural Economics and the National Statistical Office. Agricultural income, household’s debt, farmer’s literacy rate, family head’s age, infertile land, irrigated land, time period, and lower northern provinces were used as the independent factors for the farmland sales’ model. The empirical results found that six out of eight factors affected the model with differently significant levels. Among the significant factors, the household’s debt and the infertile land showed the highest significant level at 99 percent, while the farmers’ literacy rate and the lower northern provinces presented the least significant level at 90 percent. This study can be benefit to the policy-makers to determine an appropriate strategy and make it practical in order to alleviate the farmland sale’s problems in rural northern Thailand.